"Just" a fisherman's wife : a post structural feminist exposé of Australian commercial fishing women's contributions and knowledge, "sustainability", and "crisis" /: a post structural feminist exposé of Australian commercial fishing women's contributions and knowledge, "sustainability", and "crisis". (2011) - Unknown
No abstract available